A SOCIAL STUDY OF ASHES OF SCATTERED PAINTING: خواندنەكا جڤاكى بۆ ژيلەمۆيا كةڤالەكێ بژياى - Hami, Bangeen Ibrahim; Qadir, Ramazan Haji (Journal of Duhok University, 2018)
The research entitled “ a social study of ashes of scattered painting “ deals with relationship between reality and arts especially poetry . The theoretical background deals with relationship between poetry and the life of the society and the importance of this relationship. The second section deals with analyzing of collection of poems named “Ashes of a scattered painting “ by Ashty Karmeany . A lot of social foundations like poverty، unemployment، social justice  ،retardation ،disrespect  ،woman and her problems ، traditions ، love ، and corruptions were discussed as their manifestations found  in this collection.